Critical thinking and online collaborative learning in university students: a correlational study (LACCEI, 2024)
An active methodology necessary for the development of critical thinking (CT) is collaborative learning (CL). The remote modality attributes to this methodology new challenges and potentialities different from the face-to-face modality, which is why it is necessary to evolve to the online collaborative learning (OCL) approach. The objective of the study was to determine the relationship between critical thinking and online collaborative learning in university students. In this line, a descriptive and correlational analysis was carried out between these variables, using the questionnaire of critical thinking and the questionnaire online collaborative learning, that were applied to 125 higher education students from a Peruvian university. A positive and strong correlation was found between critical thinking and online collaborative learning, while in the analysis of its five dimensions, the correlation remains positive but at a medium level. It is concluded that students with a high level of online collaboration tend to have a high level of critical thinking, since dimensions such as information exchange, positive interdependence, digital skills, socio-emotional skills and internal regulation of the team foster skills that in turn are coincident with critical thinking.